Fashion beyond Versailles : Consumption and Design in Seventeenth-Century France - Bohanan, Donna, 1954- (Book collections on Project MUSE., 2012)
As the twin epicenters of style and innovation, the cities of Paris and Versailles dominate studies of consumerism in seventeenth-century France, but little scholarship exists on the material culture, fashion, and consumption patterns in the provinces. Donna J. Bohanan's Fashion beyond Versailles fills this historiographical gap by examining the household inventories of French nobles and elites in the southern province of Dauphine. As a result, she reveals a closer relationship between consumer behavior of the center and the periphery than most historians have maintained. Far-reaching in its sociological and psychological implications, Fashion beyond Versailles both makes use of and contributes to the burgeoning literature on material culture, fashion, and consumption.